Evaluation of current, force and temperature signals on welding formation of bobbin friction stir welded AA1100 - Sued, Mohammad Kamil; Zainal Abidin, Muhammad Zaimi; Mohd Nasir, Siti Noor Najihah (Penerbit Universiti Malaysia Pahang, 2021)
Understanding process response through measuring process signal provides onsite information in the area of process monitoring, which saves time and costs. The type of signals depends upon the type of process, equipment and machines used through sensors attached on the equipment used in the process. This is an important method for detecting changes in the process that reflect the condition or quality of the weld. The benefits of this method, however, has not been well performed for Bobbin friction welding. This process is different from conventional friction welding due to the different process set-up in term of tooling and parameters, hence the need to evaluate the signal response. Consequently, signal measuring for welding plate AA1100 was carried out. Tool rotation ranged from 750 rpm to 950 rpm with a fixed travel rate of 130 mm/min on a CNC milling machine and a fixed spacing tool. During the joining process, welding temperature, current consumption and welding force were measured. The resulting data were then plotted on the X-Y axis chart and mapped using the welded plate identifying the welding phase. From the welding force and current measurement, it is found that high force and current is detected at the tool entry phase and exit. As the tool moves towards the end of the plate, the temperature increased. The highest current and strength are measured when the spindle speed is at the lowest, while the highest temperature is at the fastest spindle speed In weld phase a current of © The Authors 2021.